Inovasi Sistem Pelayanan Antar Dokumen Umum Ke Rumah Warga (Si Paduka) - Artika Dhea Defitri Fitriadi; Isabella Isabella; Dwiki Adi Putra (Studi Ilmu Manajemen dan Organisasi, 2025)
Purpose: This study analyzes the implementation of the SI PADUKA (General Document Delivery System to Residents' Homes) innovation in Seberang Ulu 1 District, Palembang, aiming to reduce queues at sub-district offices and simplify access to important documents. It also examines factors hindering its implementation.Research methodology: This research uses a qualitative approach with data collected through observation, in-depth interviews, and documentation. Informants include the district head, district secretary, service staff, and residents using the SI PADUKA service. Data analysis follows three stages: reduction, presentation, and conclusion. The study applies Everett M. Rogers' innovation theory, focusing on five indicators: 1) Relative Advantage, 2) Compatibility, 3) Complexity, 4) Trialability, and 5) Observability.Results: The results show that the SI PADUKA program has been running quite effectively since March 2023. This program has a relative advantage in reducing waiting times and improving service efficiency. However, there are several obstacles in its implementation. The main obstacles are the use of personal vehicles and mobile phones by the officers, as well as complaints from the public regarding the uncertainty of document delivery times, which sometimes reach seven working days.Conclusions: The SI PADUKA innovation in Seberang Ulu 1 District, Palembang, improves efficiency by delivering documents to residents' homes. However, issues such as staff using personal vehicles and phones, along with uncertain delivery times, persist. Most residents give positive feedback, though some find the service slow.Limitations: This study faced limitations as interviews alone were insufficient for comprehensive results. To improve accuracy, the researcher added a questionnaire method, surveying 100 residents in Seberang Ulu 1, Palembang.Contribution: This research contributes to Public Service and Government Science, offering insights for future improvements and serving as a reference for students.Keywords: Innovation, Public Service, SI PADUKA, Seberang Ulu 1 DistrictHow to Cite: Defitri, A, D., Isabella, I., Putra, D, A. (2025). Inovasi Sistem Pelayanan antar Dokumen Umum ke Rumah Warga (Si Paduka). Studi Manajemen dan Organisasi, 6(1), 75-93.